DNA profiling of canarium odontophyllum miq. accessions using rapd markers - Norzaitulrina, Shamsudin (Universiti Malaysia Sarawak, UNIMAS, 2008)
DNA profiling of Canarium odontophyllum Miq. accessions was carried out using Randomly Amplified Polymorphic DNA (RAPD) markers. Five RAPD primers that generate reproducible, informative and scorable DNA profile were selected to evaluate the genetic relatedness among C. odontophyllum accessions from two different locations namely Sarikei and Sibu. 81 loci were generated. Cluster analysis was carried out using unweighted pair-group method with arithmetic averages (UPGMA) had grouped 10 C. odontophyllum samples into two main clusters. The results revealed that samples D1, SBY2, SBW1, SBW2, SBW3, D4, and D2 were in Cluster I, while samples D3, SBY3, and SBY1 were in Cluster II. Cluster I contains mixture of samples from Sarikei and Sibu, while Cluster II contains samples from Sarikei only. This may be due to those samples share common alleles. This situation may be resulted from the movement of seeds across localities. It can be concluded that these samples may be originated from the same mother trees but cultivated at different locations.